The Important Role of School Libraries in the Development of Students Information Literacy Skills - Zervas, Marios; Stavrou, Chrysanthi; Kounoudes, Alexia (Qualitative and Quantitative Methods in Libraries; 2017: Special Issue : School Library Research and Educational Resources, 2019)
The focus of this paper is on school libraries and the important role they play in the development of students’ information literacy skills. Most of the students coming from the Cyprus Education System are not aware of the content of the collection and services offered by an academic library. This problem manifests itself when students proceed to the university and find themselves struggling to locate information and material at the university’s library. The Cyprus University of Technology Library, having recognized this problem, undertook a research study to understand and evaluate the existing situation in the Cyprus Secondary Education System. The results of this research will be used to inform the decision makers, such as the Cyprus Ministry of Education, about the current situation and provide proposals for resolving this problem. This survey takes into consideration the current students’ knowledge in media literacy, including computer, media, Internet, multimedia and information literacy skills. The results of this survey are presented in this paper together with suggestions for solutions that will enable the decision makers of the education system to improve the students’ weak information literacy skills